Resource prices and planning horizons - Daniel Spiro (University of Oslo, Department of Economics, 2014)
This paper shows that a seemingly simple assumption, regarding the time horizon of economic agents, can reconcile the puzzling long run price dynamics of exhaustible resources such as oil, gas and metals. It does so by exploring the possibility that economic agents use a rolling planning horizon, meaning that they make a plan over a finite number of years but update this plan on a regular basis. This behavior can be observed in the business plans of firms, in US social security and in the extraction decisions of natural resource owners. While leaving other macroeconomic models intact, when used in models of natural resources rolling horizon planning alters the outcomes. It has the effect of removing the scarcity consideration of resource owners, thus letting only operating costs and demand determine the extraction rate. This implies that extraction will be non-decreasing and resource prices non-increasing for a long period of time and that there will be no connection between the price growth and the interest rate - in line with the trends of a majority of exhaustible resources in the last century. A calibration of the model to the oil market yields a price which closely fits the gradually falling real oil price after WWII and the sharply increasing price after 1998. It further suggests that, while long run scarcity was not an important parameter on the oil market in the 20th century, it has been important in shaping the oil price from around 1998 and onwards.
Keywords: D80; Q31; Q41; 330; Resource extraction; Oil price; Rolling horizons; Decision-making under uncertainty